2019
DOI: 10.1007/978-3-030-13417-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers’ Perception of Public Spaces and Their Practices in ICTs Uses

Abstract: The new information and communications technologies are expanding human connectivity, reconfiguring urban spatialities and generating a kind of social space that spans real and virtual, personal and impersonal, private and public. As a result, the space and time boundaries become blurred, giving rise to novel needs for, and practices of, public space usage. However, the ways in which these new practices affect public space engagement and public life in general, remain yet unclear. In addition, variations might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
3
0
2
Order By: Relevance
“…These results are in line with those of Menezes et al (2019), who found out that teens are being retreating to the virtual space due to the increasing space and mobility restrictions they face, and that teens find in social networks a new experiential place for isolation and interaction.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with those of Menezes et al (2019), who found out that teens are being retreating to the virtual space due to the increasing space and mobility restrictions they face, and that teens find in social networks a new experiential place for isolation and interaction.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there is a tendency of children s spatial and social exclusion in urban environments [84]. Often, this 'marginalization' occurs by normatively marking or differing public spaces in relation to adult space; children "are excluded from the dominant "adult" public space through controls and rules, afforded only with "leftover" or "token" spaces which are usually not sufficient to their needs" [2] (p. 111). Such a restrictive approach may also affect the relation of their everyday (social) life and public space engagement, yet the ways in which ICTs may play a role-isolation, interaction and so forth-remains unclear.…”
Section: Child-friendly Citiesmentioning
confidence: 99%
“…Captured by the momentum of the 'smart city' imaginary which denotes deep roots in, arguably, rather normative framings where technology plays a primary facilitating role and increasingly is said to underpin what it means to live in cities. Embedded into the systems and infrastructures that foster the built environment and governance dynamics, various manifestations can be detected-e.g., in patterns of consumption, socializing and service provision-that are said to, among others, reduce costs, improve insights in urban flows, spur innovation, enter new markets, and support sustainability goals [2][3][4]. The 'smart city' concept has generally been associated with "the intersection of data technologies and urban environments", while "the unique affordances of platforms are said to signal an evolution of the socio-technical relationship between citizens and cities" [5] (p. 116), what has been termed 'platform urbanism' [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Um dos principais objetivos deste pequeno estudo era que o mesmo funcionasse como um pré-teste para melhor definir questões e formas de abordar o público adolescente. Os resultados da análise foram explorados por Menezes, Arvanitidis, Smaniotto Costa & Weinstein (2018). Adicionalmente em Hannover foram questionados mais 21 adolescentes (entre 15 -16 anos) do 10º ano de escolaridade e em contexto de aula (inserido em atividade da disciplina de Inglês).…”
Section: Práticas E Usos Do Espaço E Da Tecnologia Por Adolescentes Dunclassified